Kinetics of the Photoexcited States in Thin Films of Metallo-Supramolecular Polymers With Ditopic Thiophene-Bridged Terpyridine Ligands - Menšík, Miroslav; Rais, David; Thottappali, Muhammed Arshad; Güloğlu, Pinar; Toman, Petr; Vohlídal, Jiří; Pfleger, Jiří (Frontiers in Chemistry, 2022)
Managing the excited state decay by a supramolecular structure is a crucial issue for organic photovoltaics. We show that in thin films of metallo-supramolecular polymers made of bis(terpyridine-4’-yl)terthiophenes and 〖"Zn" 〗^(2+) coupling ions, the photoexcited states generated by ultrashort laser pulses at the wavelength 440 nm decay by the bi-molecular annihilation predominantly controlled by the Förster transfer between singlet states. During this bi-molecular annihilation of singlet states, intermediate hot triplet pairs are formed, which subsequently dissociate into long-living diffusing triplet states. It explains a significant shortening of the triplet states rise time with increasing pump fluence. The diffusion coefficient of triplets showed a power-law time dependence, with its exponent proportional to the pump fluence, decreasing thus the diffusivity of triplets.